AgLED Resource Platform for Low-Emissions Development in Agriculture - Wollenberg, Eva Karoline; Costa, Ciniro; Khatri-Chhetri, Arun; Dittmer, Kyle M.; Rose, Sabrina; Shelton, Sadie W.; Rowland, Bailey; Egler, Cecelia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
What is AgLED?